Information, persuasion, and control in moral appraisal of advertising strategy - Durham, Taylor R. (Journal of business ethics, 1984)
The formulation of moral issues surrounding consumer advertising tends to focus on the capacity to persuade or inform, and how these capabilities may be used to distort or fulfill needs and desires. Discussion of these issues abstracts from widespread advertising and marketing practices, by assuming that all advertising is mass advertising, broadcast indiscriminately over the entire market population. This assumption directs attention away from important issues stemming from actual advertising strategies, which involve campaigns designed for and conveyed to particular customer groups or segments within broader product market. Several cases are outlined to illustrate the class of practices considered to be important and usually ignored, and issues that they raise for moral appraisal are suggested.